Keanekaragaman Fitoplankton di Sungai Kabupaten Banyuasin - Ramadhan, Riska; Teristiandi, Novin; Fatiqin, Awalul (Pusat HKI, Paten, dan Publikasi Ilmiah Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to determine the diversity of phytoplankton in the river in Banyuasin Regency. Phytoplankton samples were taken using an active sampling method using a plankton net in an upright position on the water surface. The results of the study obtained five classes consisting of 32 species of phytoplankton. The highest abundance was at station II in the morning as many as 684 individuals/l and the lowest abundance was at station I in the morning with an abundance of 286 individuals/l. The most dominant diversity was found in Planktothrix sp species and when viewed from the abundance value the most dominant species were Phacus cloroplate, Trachelomonas lacustris, Diatoma elongatum, Ankistrodesmus falcatus, and Pediastrum tetras species. The results of the analysis show that the abundance of a phytoplankton has a close relationship with the physico-chemical parameters in a waters.AbstrakPenelitian ini bertujuan untuk untuk mengetahui keanekaragaman fitoplankton di Sungai di Kabupaten Banyuasin. Pengambilan sampel fitoplankton menggunakan metode sampling aktif menggunakan plankton net dengan posisi tegak lurus pada permukaan air. Hasil penelitian diperoleh lima kelas yang terdiri dari 32 spesies fitoplankton. Kelimpahan tertinggi terdapat pada stasiun II pagi hari sebanyak 684 Individu/l dan kelimpahan terendah terdapat pada stasiun I pada pagi hari dengan kelimpahan sebanyak 286 individu/l. Keanekaragaman yang paling dominan terdapat pada spesies Planktothrix sp dan jika dilihat dari nilai kelimpahan nya spesies yang paling dominansi terdapat pada spesies Phacus cloroplate, Trachelomonas lacustris, Diatoma elongatum, Ankistrodesmus falcatus, dan Pediastrum tetras. Dari hasil analisis memperlihatkan bahwa kelimpahan pada suatu fitoplankton memiliki kaitan erat dengan parameter fisika-kimia pada suatu perairan.